Gpr125 Marks Distinct Cochlear Cell Types and Is Dispensable for Cochlear Development and Hearing - Sun, Haiying; Wang, Tian; Atkinson, Patrick J.; Billings, Sara E.; Dong, Wuxing; Cheng, Alan G. (Frontiers in Cell and Developmental Biology, 2021)
The G protein-coupled receptor (GPR) family critically regulates development and homeostasis of multiple organs. As a member of the GPR adhesion family, Gpr125 (Adgra3) modulates Wnt/PCP signaling and convergent extension in developing zebrafish, but whether it is essential for cochlear development in mammals is unknown. Here, we examined the Gpr125lacZ/+ knock-in mice and showed that Gpr125 is dynamically expressed in the developing and mature cochleae. From embryonic day (E) 15.5 to postnatal day (P) 30, Gpr125-β-Gal was consistently expressed in the lesser epithelial ridge and its presumed progenies, the supporting cell subtypes Claudius cells and Hensen’s cells. In contrast, Gpr125-β-Gal was expressed transiently in outer hair cells, epithelial cells in the lateral cochlear wall, interdental cells, and spiral ganglion neurons in the late embryonic and early postnatal cochlea. In situ hybridization for Gpr125 mRNA confirmed Gpr125 expression and validated loss of expression in Gpr125lacZ/lacZ cochleae. Lastly, Gpr125lacZ/+ and Gpr125lacZ/lacZ cochleae displayed no detectable loss or disorganization of either sensory or non-sensory cells in the embryonic and postnatal ages and exhibited normal auditory physiology. Together, our study reveals that Gpr125 is dynamically expressed in multiple cell types in the developing and mature cochlea and is dispensable for cochlear development and hearing.